Analisis Risiko Kredit Pada Pt. Bank Rakyat Indonesia (Persero) Tbk Cabang Tanah Grogot Unit Batu Kajang Periode 2012-2014 (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
The purpose of this study to determine the credit risk on the PT. Bank Rakyat Indonesia (Persero) Tbk Cabang Tanah Grogot Unit Batu Kajang with the period 2012-2014 were evaluated from the ratio of NPL (Non Performing Loan), LDR (Loan to Deposit Ratio) and CAR (Capital Adequacy Ratio). This study uses quantitative research and type of research used by analyzing data that originates in the financial statements of PT. Bank Rakyat Indonesia (Persero) Tbk Cabang Tanah Grogot Unit Batu Kajang by determining whether categorized as current or noncurrent loans. Credit risk is the risk of loss resulting from the failure of debtors who can not meet its obligations. There are three ratios used to analyze credit risk at PT Bank Rakyat Indonesia (Persero) Tbk Cabang Tanah Grogot Unit Batu Kajang accordance with standard BI. Based on the analysis we concluded that the results of the 2012-2014 NPL result fluctuated but remained in the standard BI below 5% and categories including liquid credit. LDR of the year 2012-2014 results are constantly increasing, but the bank can not meet that standard BI 85-100% lower bank liquidity, and credit risks at banks is small. CAR from 2012-2014 year results are fluctuated but remained above the standard BI 8%, and credit risks faced by small.